Use the following step as a guide to solve the following equationWrite out your work for all steps to solve the equation . 2x - 5 = 3(4x + 5)

1 answer

To solve the equation \( 2x - 5 = 3(4x + 5) \), we'll follow these steps:

Step 1: Expand the right side

First, we need to distribute the 3 on the right side of the equation:

\[ 3(4x + 5) = 3 \cdot 4x + 3 \cdot 5 = 12x + 15 \]

Now we can rewrite the equation:

\[ 2x - 5 = 12x + 15 \]

Step 2: Move all terms involving \( x \) to one side

Next, we want to move all terms involving \( x \) to one side of the equation and constant terms to the other side. We can do this by subtracting \( 12x \) from both sides:

\[ 2x - 12x - 5 = 15 \]

This simplifies to:

\[ -10x - 5 = 15 \]

Step 3: Move the constants to the other side

Now, we can add 5 to both sides to isolate the term with \( x \):

\[ -10x - 5 + 5 = 15 + 5 \]

This simplifies to:

\[ -10x = 20 \]

Step 4: Solve for \( x \)

Now, we divide both sides by -10 to solve for \( x \):

\[ x = \frac{20}{-10} = -2 \]

Solution

Thus, the solution to the equation \( 2x - 5 = 3(4x + 5) \) is:

\[ \boxed{-2} \]

Similar Questions
  1. Izzie is trying to solve this inequality: 3(t+1)−4t≥−5After she solves it, she shows it to you and asks you if she did it
    1. answers icon 1 answer
    1. answers icon 1 answer
  2. Josephine solved a quadratic equation: (x+6)^2=49. Her work is shown below.Step 1: √(x+6)^2 = √49 Step 2: x+6 = 7 Step 3: x
    1. answers icon 2 answers
  3. Consider the sequence of steps to solve the equation:5(x - 3) = 7x2 Step 1 ⇒ 10(x - 3) = 7x Step 2 ⇒ 10x - 30 = 7x Step 3
    1. answers icon 3 answers
more similar questions